Online Arabic Language Teaching Model Based on Collaborative Learning in Indonesian Senior High Schools - Umamah, Maftuhatul; Hifdhiyah, Maulidatul (Institut Agama Islam Negeri Palangka Raya, 2024)
This research focuses on the implementation of online/virtual Arabic language learning at Darul Quran Senior High School in Mojokerto, utilizing the collaborative-based learning model known as